Image of Late Antique Rome and the Popes in the "Chronicle" of George the Monk - Kosiński, Rafał (Vox Patrum, 2026)
The purpose of this article is to analyse the picture of late antique Rome and the papacy as outlined in the ninth century in the pages of the Chronicle of George the Monk. As a result, it can be concluded that the Byzantine chronicler’s interest in Rome drastically declines as Emperor Constantine begins to reside in Constantinople. With the return of Emperor Theodosius I from Italy to the Bosporus, George the Monk pays little attention to events in the West, the only exception being the emphasised leading role of the Bishop of Rome within the pentarchy system, especially during the subsequent Councils. However, this applies only to the version of the so-called vulgata, while the version known from the manuscript Coislinianus 305 ignores almost completely the role of the pope in the ecclesial system of the empire.